O escaravelho do diabo na formação de leitores: uma proposta de letramento literário - Sildilene Batista Lamim Oliveira (2021)
This research is about the elaboration of a Basic Sequence of literary literacy, with adaptation of the Expanded Sequence, and seeks to contribute to the literary formation of students. To this objective, it was elaborated readings activities of a detective story, an adapted film and reviews that sensitize the reader and that favor not only critical thinking about ethical, political, social and ideological issues, but also the analysis of linguistic strategies of text construction. In meetings during the regular class period, students will be able to discover the following works: the detective story O escaravelho do diabo, by Lúcia Machado de Almeida and its cinematographic adaptation; the thriller and adventure film O escaravelho do diabo, by director Carlo Milani. In addition, they will be able to deepen their knowledge and produce writings of radio reviews to be read on community radio, indicating literary reading. Methodologically, this research has a qualitative and purposeful feature, once it starts from the identification of a problem detected by the teacher-researcher in the educational context in which she is inserted and can be developed in classes of the 9th grade of elementary school in public schools. The present research intends to answer the following question: would the literary literacy proposal, aiming at literary formation, through the basic sequence, be able to insert the student in the world of books and see in literature a humanizing power? Once the question has been formulated, the initial hypothesis is that the narrative structure of the detective novel, centered on investigation and the discovery play, arouses students' desire and curiosity to try other books, as well as the dialogical relationships between text and reader and that with the cinematographic production are able to motivate and stimulate the practice of reading and writing. The activities will be mediated by the teacher and it is hoped that, at the end of the project, it will be possible to form a “Book Circle” and transform the school into a space for literary reading. The theoretical reference of this research is based on CANDIDO (2004), as it proposes a humanizing and social view of literature; COSSON (2009 and 2019), which presents the importance of literary literacy for the schooling of literature, promotion of literary reading in the classroom; SILVA (2005) and COLOMER (2007), who defend the formation of readers by the school. For presenting relevant themes for the elaboration and implementation of this project, other authors were read, as: BAKHTIN (1988), novel; FREIRE (1989), reading of the world and of words; BALTAR (2012), radio presentation; REIMÃO (1983), SILVA (2009) and NUNES (2014), detective novel; DELL ’ISOLA (2007), retextualization of textual genres; GERALDI (2012), meaningful textual production; HERNÁNDEZ (1998), reorganization of the curriculum by work projects and NAPOLITANO (2011), use of films in the classroom. Thus, it is hoped that the basic sequence produced can be used in order to contribute to the approximation of students to literary books and to the promotion of their literary literacy, making them voluntary and autonomous readers.